2006
DOI: 10.1016/j.jastp.2005.02.031
|View full text |Cite
|
Sign up to set email alerts
|

TIMED Doppler interferometer (TIDI) observations of migrating diurnal and semidiurnal tides

Abstract: Based on zonally averaged TIDI meridional wind data from one yaw period (2004079 -140) during equinox, we examine the latitudinal and altitudinal distribution of the migrating diurnal and semi-diurnal tides using least squares fitting method to provide a global view of these tidal waves. The TIDI results are compared with Global Scale Wave Model 00 output for the month of April. The diurnal tide amplitude distribution and are in a good agreement. The TIDI results show a lower peak altitude (97 km) while GSWM00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 31 publications
4
59
2
Order By: Relevance
“…The TIDI observations extend from pole to pole, capable of continuous day-night coverage between 80 and 105 km [ Killeen et al , 2006; Wu et al , 2006]. Spectral analysis of TIDI horizontal wind measurement variances by Yue et al [2013b] found uncertainties on the order of 2 m s −1 or less.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TIDI observations extend from pole to pole, capable of continuous day-night coverage between 80 and 105 km [ Killeen et al , 2006; Wu et al , 2006]. Spectral analysis of TIDI horizontal wind measurement variances by Yue et al [2013b] found uncertainties on the order of 2 m s −1 or less.…”
Section: Methodsmentioning
confidence: 99%
“…Residuals of DW1 will also be present, particularly at midlatitudes or during times of reduced sampling at low latitudes as mentioned previously. The former contamination should be mostly negligible as the peaks of DW1 in the MLT zonal wind fields are located around ± 20° latitude [ Wu et al , 2006]. While the latter cannot be entirely suppressed, the interannual consistency in the background zonal wind results shown later indicate that they do not dominate over QTDW-related changes.…”
Section: Methodsmentioning
confidence: 99%
“…Amplitudes and phases of the semidiurnal tides have been recently derived from SABER/TIMED and MLS/UARS temperature measurements (Forbes and Wu, 2006;Zhang et al, 2006). Wu et al (2006) examined the migrating semidiurnal tide based on TIDI/TIMED wind measurements. Oberheide et al (2007) analyzed the horizontal winds measured by TIDI/ TMED and presented climatologies of monthly mean amplitudes and phases for six nonmigrating semidiurnal tidal components between 85 and 105 km altitude and between 451S and 451N latitude (westward propagating wavenumbers 4, 3 and 1, the standing oscillation with wavenumber 0 and eastward propagating wavenumbers 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…the interactions between different tidal components presented by Teitelbaum et al (1989), Smith (2000) and , tides and planetary waves by and Mayr et al (2003) and tides and gravity waves by and Lu and Fritts (1993). These interactions may also lead to the disagreement of the observed tidal amplitudes with the GSWMs at altitudes above 90 km (Burrage et al, 1995;Palo et al, 1997;Bruinsma et al, 2002;Grieger et al, 2002;Pancheva et al, 2002;She et al, 2003;Batista et al, 2004;Wu et al, 2006), in addition to the nonlinear interactions discussed in this paper. The very large alterations in the background temperature (57.9 K and −52.9 K) deduced from our nonlinear model may be due to the absent of these dissipation mechanisms.…”
Section: Discussionmentioning
confidence: 67%
“…We can see that in most regions of the Northern Hemisphere, the variation is negative and very strong, which means that the meridional-wind amplitudes of the semidiurnal tide from our nonlinear model are smaller than the GSWM-00 and consistent with the observations. Wu et al (2006) compared the TIDI observations with the GSWM-00 output for April between 85 and 110 km, and found that the Southern Hemisphere amplitudes shown by the TIDI data are much weaker than those predicted by the GSWM-00. Here, for comparison, we presented the nonlinearity-induced amplitude difference of the meridional semidiurnal tide during April (right panel of Fig.…”
Section: Discussionmentioning
confidence: 99%